Early detection of brain death using the Bispectral Index (BIS) in patients treated by extracorporeal cardiopulmonary resuscitation (E-CPR) for refractory cardiac arrest. (November 2017) - Jouffroy, Romain; Lamhaut, Lionel; Guyard, Alexandra; Philippe, Pascal; An, Kim; Spaulding, Christian; Baud, Frédéric; Carli, Pierre; Vivien, Benoît
Abstract: Background: Despite increasing use of extracorporeal cardiopulmonary resuscitation (E-CPR) for treatment of refractory cardiac arrest patients, prognosis remains dismal, often resulting in brain-death. However, clinical assessment of brain-death occurence is difficult in post-cardiac arrest patients, sedated, paralyzed, under mild therapeutic hypothermia (MTH). Our objective was to assess the usefulness of Bispectral-Index (BIS) monitoring at bedside for an early detection of brain-death occurrence in refractory cardiac arrest patients treated by E-CPR. Methods: This prospective study was performed in an intensive care unit of an university hospital. Forty-six patients suffering from refractory cardiac arrest treated by E-CPR were included. BIS was continuously recorded during ICU hospitalization. Clinical brain-death was confirmed when appropriate by EEG and/or cerebral CT angiography. Results: Twenty-nine patients evolved into brain-death and had average BIS values under MTH and after rewarming (temperature ≥35 °C) of 4 (0–47) and 0 (0–82), respectively. Among these, 11 (38%) entered into a procedure of organs donation. Among the 17 non-brain-dead patients, the average BIS values at admission and after rewarming were 39 (0–65) and 59 (22–82), respectively. Two patients had on admission a BIS value equal to zero and evolved to a poor prognostic (CPC 4) and died after care limitations. BIS values were significantly different between patients who developed brain death and those who did not. In both groups, no differences were observed between the AUCs of ROC curves for BIS values under MTH and after rewarming (respectively 0.86 vs 0.83, NS). Conclusions: Initial values of BIS could be used as an assessment tool for early detection of brain-death in refractory cardiac arrest patients treated by mild therapeutic hypothermia and E-CPR.